2010
DOI: 10.1002/hlca.200900375
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations of an Acetone‐Based BriggsRauscher System by α‐Tocopherol (Vitamin E)

Abstract: The malonic acid (MA)-based oscillating Briggs -Rauscher reaction (BR) in batch mode has been shown to be sensitive to various hydrophilic polyphenol antioxidants. Several of these have been shown to cause cessation of oscillations for a period of time before a restart occurs. The length of time before oscillations restart is related to the type of antioxidant and its concentration. Procedures have been devised to use this method as a tool for measuring antioxidant activity from pure compounds and from extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This method was used because the pH of BR reaction is about 2, which is similar to that of the fluids of the main digestive process (human stomach). This can give us in vitro information on antioxidant activity at “real digestion conditions” and can help in assessment of nutrition for maintenance of health and prevention of diseases (Cervellati, Furrow, Grecoa, Honer, & Venturi, 2010; Cervellati, Honer, Furrow, Needens, & Costa, 2001; Honar & Cervellati, 2002). In BR reaction, the antioxidant efficacy of potato peel extract is expressed as the length of inhibition time ( t inhibition ) in seconds before oscillation restart.…”
Section: Resultsmentioning
confidence: 99%
“…This method was used because the pH of BR reaction is about 2, which is similar to that of the fluids of the main digestive process (human stomach). This can give us in vitro information on antioxidant activity at “real digestion conditions” and can help in assessment of nutrition for maintenance of health and prevention of diseases (Cervellati, Furrow, Grecoa, Honer, & Venturi, 2010; Cervellati, Honer, Furrow, Needens, & Costa, 2001; Honar & Cervellati, 2002). In BR reaction, the antioxidant efficacy of potato peel extract is expressed as the length of inhibition time ( t inhibition ) in seconds before oscillation restart.…”
Section: Resultsmentioning
confidence: 99%
“…Reference [37] confirmed that polyphenols could be oxidized into quinones, so tannic acid could be oxidized into quinone. As tannic 3 to represent tannic acid. The reaction between tannic acid and BrO 2 · with the formation of quinone is shown in reaction (8).…”
Section: Mechanism Of Action Of Tannic Acid On the Oscillation Systemmentioning
confidence: 99%
“…This type of system has attracted the attention of researchers [2][3] due to its potential applications in theoretical and practical chemistry since the first model for an oscillating chemical system was established [4]. Among all oscillating systems, both classical Belousov-Zhabotinskii (BZ) type of reaction [5][6][7][8] and Briggs-Rauscher (BR) type of reaction [9][10] have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%